Exploring The Antioxidant and Antimicobial Potential of Some Scandix species - İnci, Şule; Kırbağ, Sevda; Demirpolat, Azize; Bağci, Eyup (Artvin Çoruh Üniversitesi, 2026)
The use of plant-based preparations is an ancient practice that has persisted from the past to the present. In particular, their use as antimicrobial and antioxidant agents has been increasingly common. This study aims to determine the antimicrobial and antioxidant effects of methanol extracts of the aerial parts of 5 Scandix species (S. iberica, S. stellata, S. pecten veneris, S. macrorhyncha and S. balansae) collected from Türkiye. The antimicrobial effects of the methanol extracts were detected by using the disk diffusion method. Antioxidant activity also were evaluated by measuring total antioxidant capacity, total oxidant status, and DPPH radical scavenging activity. The methanolic extract of Scandix species has inhibited the growth of the microorganisms at the 14.6 to 35.3 mm ratio. TAS values ranged from 2.0 to 3.4 mmol, while TOS values ranged from 15.1 to 23.7 ?mol. It was observed that the DPPH radical scavenging effects increased with rising concentrations. The results will contribute to the evaluation of the potential of these species as natural antimicrobial and antioxidant compounds in the food, cosmetic or pharmaceutical industries.

Bitkisel preparatların kullanımı geçmişten günümüze kadar devam eden eski bir uygulamadır. Özellikle antimikrobiyal ve antioksidan ajan olarak kullanımı giderek yaygınlaşmaktadır. Bu çalışmada, Türkiye'den toplanan 5 Scandix türünün (S. iberica, S. stellata, S. pecten veneris, S. macrorhyncha and S. balansae) toprak üstü kısımlarının metanol ekstraktlarının antimikrobiyal ve antioksidan etkileri belirlenmesi amaçlanmaktadır. Metanol ekstraktlarının antimikrobiyal etkileri disk difüzyon yöntemi kullanılarak tespit edilmiştir. Antioksidan aktivite ayrıca toplam antioksidan kapasite (TAS), toplam oksidan durum (TOS) ve DPPH radikal süpürücü aktivitesi ölçülerek değerlendirilmiştir. Scandix türlerinin metanol ekstraktının mikroorganizmaların büyümesini 14.6 ila 35.3 mm oranında engellediği tespit edilmiştir. TAS değerleri 2.0 ila 3.4 mmol arasında değişirken, TOS değerleri 15.1 ila 23.7 ?mol arasında değişmiştir. DPPH radikal süpürücü etkilerinin artan konsantrasyonlarla arttığı gözlemlenmiştir. Elde edilen sonuçlar, Scandix türlerinin gıda, kozmetik veya ilaç endüstrilerinde doğal antimikrobiyal ve antioksidan bileşikler olarak kullanım potansiyelinin değerlendirilmesine katkıda bulunacaktır.
Scandix Türlerinin Antioksidan ve Antimikrobiyal Potansiyellerinin Araştırılması
Keywords: Plant Biotechnology; Bitki Biyoteknolojisi